Treatment of landfill leachate by advanced oxidation processes - Koçak, Seda; Güney, Cansu; Argun, M. Tuna; Tarkın, Begüm; Kırtman, E. Özlem; Akgül, Deniz; Mertoglu, Bulent (Marmara Üniversitesi Fen Bilimleri Dergisi, 2013)
Organic and inorganic pollutants found in municipal landfill leachate lead to severe problems for the environment when directly discharged to water bodies without treatment. Due to the existence of recalcitrant organics in leachate, advanced oxidation processes (AOP) are mostly applied to biologically treated leachate as a polishing step. In this study, the effectiveness of Fenton process on leachate treatment was examined. The Fenton process was applied to both young (untreated) and biologically treated leachate provided from Şile Kömürcüoda Landfill in Istanbul. It was treated by using up flow anaerobic sludge blanket (UASB) reactor and membrane bio-reactor (MBR) processes respectively prior to AOP application. In addition, the combination of Ultraviolet (UV)/Fenton and Ultrasound (US)/Fenton processes were applied to biologically treated leachate to improve the efficiency of Fenton process. The results suggested that, Fenton process is an efficient oxidation method for the treatment of organic matter and color in leachate. It was able to remove 70 % chemical oxygen demand (COD) from the raw leachate, while for biologically treated leachate the COD removal was over 50 %. On the other hand, color removal was observed to be 90 % and 98% in old and young leachate respectively. It was also seen that the additional treatment techniques used in the study did not improve the treatment efficiency of Fenton process.
Keywords: Leachate; AOPs; Fenton; UV; US